ANALISIS LIRIK LAGU "DIRI" KARYA TULUS MENURUT TEORI HERMENEUTIKA GADAMER - Marisa Septiana Situmeang; Erlika Tampubolon; Azza Akira Syakirina; Putri Sidabutar; Jakaria (Jurnal Genta Mulia, 2025)
Songs are a form of artistic expression that not only conveys emotional messages, but also reflects philosophical values and reflections on life. The song "Diri" by Tulus raises the theme of identity search and self-acceptance, which can be interpreted in various ways by listeners. This study aims to analyze the lyrics of the song "Diri" using Gadamer's hermeneutics approach, which emphasizes the dialogue between the text and the meaning. Using the concept of horizon fusion, this study explores how the meaning of songs is formed through the interaction between the experience of the songwriter and the listener's perspective. The results of the analysis show that this song conveys a message about the importance of making peace with yourself, appreciating the journey of life, and letting go of past wounds in order to achieve inner peace. The findings of the study also show that the meaning of songs is dynamic, depending on the background and experience of the individual who listens to them. Thus, this study not only enriches the study of hermeneutics in music, but also provides insight into how song lyrics can be a medium of deep self-reflection.